Effect of Ratio of Soursop with Papaya and Arabic Gum Addition on The Quality of Fruit Leather - Edy Syahputra Harahap; Terip Karo-Karo; Linda Masniary Lubis (Universitas Sumatera Utara, 2015)
The aim of this research was to find the effect of ratio of soursop with papaya pulps and several arabic gum addition on the quality of mixture of soursop and papaya fruit leather. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e. :ratio of soursop with papaya pulps (S) : (70% : 30% ; 60% : 40% ; 50% : 50% ; 40% : 60% ; 30% : 70%) and arabic gum concentration (G): (0,6%, 0,8%, and 1%). Parameters analyzed were moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid, score of organoleptic values of colour, taste and texture and hedonic of organoleptic values of colour, taste, flavour and texture. The results showed that the ratio of soursop with papaya pulps had highly significant effect on moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid, score of organoleptic values of colour, taste, texture, and hedonic of organoleptic values of colour, flavor, taste and texture. Arabic gum concentration had highly significant effect on moisture content, crude fiber content, and had significant effect on vitamin C content, total acid. Interactions of the two factors had significant effect on moisture content. The ratio of soursop with papaya pulps of (30% : 70%) and arabic gum concentration of (1%) produced the best quality of fruit leather and more acceptable. Keywords : Soursop, Papaya, Arabic gum, Fruit leather.